The Inheritance of a Wife Who Has Been Divorced and whose Iddah Period Has Ended Perspective of the Imam Syafi'i School (Case Study in the Mining Community of Mandailing Natal Regency) - Abdul Hakim; Paijal Usrin Siregar; Bismillahi Ahya (ISNU Sumatera Utara, 2025)
The Tambangan Jae community adheres to the Shafi'i school of thought, but in the distribution of inheritance to a divorced wife whose iddah has expired, the Tambangan Jae community has a different view. This research is a juridical empirical study using a case study approach. The results of this study indicate that the opinions and practices of the Tambangan Jae community regarding the inheritance of a divorced wife whose iddah has expired differ from the opinions of the Shafi'i school of thought, motivated by several factors. First, the customs practiced by the community for generations. Second, as a form of protection for women and children. Third, the wife participates in working to meet household needs, so that the wife still receives a share of the inheritance from her husband's assets.